Design and Research on Multifunctional Dredging Machine for Urban Sewer - Tian, Aoxiang; Yang, Yanfang; Shen, Yifan; Liang, Peijun; Hu, Xueqing; Yang, Menglan; Liu, Zili; Li, Yongchao (Journal of physics. Conference series, 2020)
The drainage pipeline is responsible for the collection and transportation of urban sewage and wastewater, and is one of the necessary facilities for the normal operation of the city. Therefore, it is of great significance to unblock and prevent the sewer pipe. A new type of dredging machine is designed to overcome the defects of the existing dredging method. The machine consists of two parts: a mechanical module and a control module. The machine adopts the idea of mechatronics which realize the automatic operation of the multi-function dredging machine, and it has low cost and good market economy benefits.